Analysis of Economic Policy in the Middle East in the Classical and Contemporary - Ardianto Bayu Wibowo; Yon Machmudi; Muhammad Hamdan Basyar (Publik : (Jurnal Ilmu Administrasi), 2022)
The purpose of this study is to analyze the economic system in the Middle East based on the available literature. The research method used is content analysis in the type of semiotic analysis. This type of semiotic content analysis method is considered in accordance with the data used by researchers, namely literature or text, both verbal and nonverbal. The results of this study indicate that the economic system in the Middle East is considered dynamic. This condition occurs to compensate for the complex problems in the region. However, among 10 countries in the Middle East, only Syria is closed about the economic system used by its country. The economic system in the Middle East does not seem to be fixated on the long history of the development of economic thought in the early days of Islam, the arrival of Western colonialism, the emergence of nation states in the Middle East, to the explosion of the potential wealth of natural resources of the Middle East in contemporary times